ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN ANTENATAL CARE PADA IBU HAMIL DI ERA PANDEMI COVID-19 DI PUSKESMAS BIRU-BIRU KEC. BIRU-BIRU KAB. DELI SERDANG TAHUN 2022 - Widia royanda Widia royanda Widia royanda (Jurnal Inovasi Kesehatan Masyarakat, 2022)
ANC is a policy that is carried out in an effort to prevent the increase in maternal and infant mortality in indonesia, namely by provoding maternal and child health services in facilities. The second pillar of ANC ams to prevent complication and ensure that there are no complications in pregnancy. This study aims to analyze the factors that influence antenatal care visits in the era of the covid-19 pandemic at the Biru-Biru Public health centre, Biru-Biru District, Deli Serdang Regency. This study aims to analyze the factors that influence the visit Antenatal Care in the times of pandemic covid-19 in Puskesmas Biru-Biru Kecamatan Biru-Biru Kbupaten Deli Serdang. Types of research kuantitatif with desain case control. The sampling technique in this study used the method perposive sampling with Lameshow formula. The sample of this study used 88 samples, consisting of 44 case samples and 44 control samples optained from lameshow formula. Based on the statistical tests carried out, the value of the factor that most influenced pregnant women during the COVID-19 pandemic was obtained, namely the husband’s support factor with a value of B = 3.81, P value = 0.000, OR = 45.519, 95%Cl = 8.725-237.490. It is hoped that the Puskesmas officers will continue to motivate husbands who have pregnant wives to provide support to mothers to do ANC. Such as making whatsapp groups with pregnant women together with their husbands and Puskesmas officers. Sending digital posters via whatsapp about the importance of doing pregnancy tests to determine the development of the baby in the womb. It is hoped that husbands can provide strong support to mothers during pregnancy to maintain health during pregnancy so that maternal health during pregnancy can be monitored and mothers get maximum health services from health workers.